ANALISIS TINDAK TUTUR EKSPRESIF PADA DAFTAR PUTAR VIDEO KULIAH NEGOSIASI DALAM CHANNEL YOUTUBE KULIAH KEHIDUPAN - Utomo, Asep Purwo Yudi; Azki Akhmad Mafaza; Novana Ika Puspita; Fadhila Ramadhani; Diyas Bagus Firmansyah; Riyadi Widhiyanto; Rossi Galih Kesuma (Universitas Terbuka, 2024)
Pragmatics is a field of linguistic study that relies on context as the main means of understanding an intention. One of its areas of study is expressive speech acts, which are used to express or convey someone's emotional and feeling states. The aim of this research is to describe and analyze various types of expressive speech acts found in the